Polyphenol stability and antioxidant capacity of various sweetened dried cranberries and cranberry supplements - Kovacev, Kara (Kansas State University, 2019)
Cranberries are fruits rich in polyphenols known to promote health in various ways, from urinary tract health to cardiovascular and oral health. As consumers look to reduce calories and sugar and move to more convenient snacking and bioactive food forms, research on different forms of cranberries and stability of bioactive compounds over time becomes more important. There is a lot of research on stability of polyphenols in cranberry juice drinks, however, similar research on sweetened dried cranberries and cranberry supplements is a needed research area. This research focused on the effects of product matrix, processing, and packaging on polyphenol stability and antioxidant capacity of various sweetened dried cranberries and cranberry supplements over time. Across the sweetened dried cranberry treatments, it was found that product matrix significantly influenced not only initial polyphenol content but also degradation over time. Sliced cranberries had higher polyphenol content than whole cranberries due to higher infusion rate via increased surface area. Infusion ingredients also impacted polyphenol content and stability, with additional bulking agents, such as apple concentrate or soluble corn fiber, providing enhanced insulation and stability of polyphenols during processing compared to sucrose-only treatments. Compared to raw cranberries, sweetened dried cranberries are significantly lower in polyphenols. Measurement of antioxidant capacity via DPPH assay found that sweetened dried cranberries had similar antioxidant capacity to raw cranberries, though other studies analyzing cranberries via ORAC assay resulted in higher antioxidant values for raw cranberries demonstrating the importance of consistency in assay when comparing values. Across the cranberry supplement treatments, it was found that the spray-dried treatment had significantly higher initial and final polyphenol content as well as stability for all analyses over time compared to gummy treatments. Compared to raw cranberries, the spray-dried treatment had significantly more polyphenols and antioxidant activity, further signifying that spray-drying stabilizes polyphenols due to lower moisture content and Aw, leads to a higher concentration of active components due to water removal, and the capsule form further protects polyphenols from degradation. Across gummy treatments, product matrix and packaging impacted not only initial polyphenol content but also stability over time. The gummy treatment with fewer filler ingredients contained a higher ratio of polyphenols and higher stability (except for proanthocyanidins) due to being packaged as individual wrapped gummies compared to bulk for the other gummy treatment. Overall this research demonstrates that product matrix in conjunction with processing parameters and packaging for sweetened dried cranberries and cranberry supplements significantly impacts polyphenol content and stability. The product with the highest polyphenol content and most stability over time was the spray dried supplement, though as consumers seek bioactive foods instead of supplements the sliced soluble corn fiber, glycerin, sucrose, and sucralose infused sweetened dried cranberry and gummy with few filler ingredients may be preferable options. Further research should be done to evaluate how different processing conditions, packaging, and other product matrix attributes may improve polyphenol content and stability of non-spray dried cranberry products over time.
Keywords: Polyphenol; Cranberry; Proanthocyanidin; Anthocyanin